MEASUREMENT OF THE EFFECTIVENESS STRATEGY IS/IT TO BUSINESS STRATEGY WITH IT BALANCED SCORECARD METHOD AT BINUS INTERNATIONAL JOSEPH WIBOWO CENTER - Wijaya, Hendy; Carolina, Erny (Infotech: Journal of Technology Information, 2020)
JWC is a campus line from Binus University that supports international standard management and business with the management of the academic development framework-EQUIS. To be able to work together and compete in a globalized world also requires the provision of operational facilities that are supported by the provision and management of information technology. The problem in this study is that companies are implementing an IS / IT strategy but not in accordance with their business strategy. If the strategy used cannot really be done, bankruptcy. The purpose of this research is to study whether the IS / IT strategy refers to the JWC business strategy. Measurement of the compatibility of the IS / IT strategy with this business strategy uses the IT Balance Scorecard, SWOT method to support strategic planning, and the Analytical Hierarchy Process method in determining the importance of interest. Data collection methods used were observation, interviews, literature study, questionnaires. The agreed outcome is an agreement consisting of the best IT SI SI strategy that supports JWC's business strategy.